Quantification of Carbonic Anhydrase Inhibitors and Metabolites in Urine and Hair of Patients and Their Relatives - Lo Faro, Alfredo Fabrizio; Tini, Anastasio; Bambagiotti, Giulia; Pirani, Filippo; Faragalli, Andrea; Carle, Flavia; Pacella, Elena; Ceka, Artan; Moretti, Marco; Gottardi, Massimo; Lassandro, Nicola Vito; Nicolai, Michele; et al. (Biology (Basel, Switzerland), 2022)
Carbonic anhydrase inhibitors (CAIs) are prescription drugs also used in doping to dilute urine samples and tamper with urinalyses. Dorzolamide, brinzolamide, and acetazolamide are prohibited by the World Anti-Doping Agency. Detecting CAIs and their metabolites in biological samples is crucial to documenting misuse in doping. We quantified dorzolamide, brinzolamide, acetazolamide, and their metabolites in the urine and hair of 88 patients under treatment for ocular hypertension or glaucoma. Samples of the patients’ relatives were analyzed to assess potential for accidental exposure. After washing, 25 mg hair was incubated with an acidic buffer at 100 °C for 1 h. After cooling and centrifugation, the supernatant was analyzed by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Urine (100 μL) was diluted and centrifuged before UHPLC-MS/MS analysis. Run time was 8 min through a reverse-phase column with a mobile phase gradient. MS/MS analysis was performed in a multiple-reaction monitoring mode after positive electrospray ionization. Median urinary concentration was 245 ng/mL (IQR: 116.2–501 ng/mL) for dorzolamide, 81.1 ng/mL (IQR: 35.9–125.3 ng/mL) for N-deethyl-dorzolamide, 0.77 ng/mL (IQR: 0.64 ng/mL–0.84 ng/mL) for N-acetyl-dorzolamide, 38.9 ng/mL (IQR: 20.4–79.2 ng/mL) for brinzolamide, and 72.8 ng/mL (IQR: 20.7–437.3 ng/mL) for acetazolamide. Median hair concentration was 0.48 ng/mg (IQR: 0.1–0.98 ng/mg) for dorzolamide, 0.07 ng/mg (IQR: 0.06–0.08 ng/mg) for N-deethyl-dorzolamide, 0.40 ng/mL (IQR: 0.13–1.95 ng/mL) for brinzolamide. Acetazolamide was detected in only one hair sample. Dorzolamide and brinzolamide were detected in the urine of three and one relatives, respectively. Cutoff concentrations of urinary dorzolamide and brinzolamide are necessary to preclude false positives due to contamination or passive exposure. We reported the first concentrations of brinzolamide in hair.